2020
DOI: 10.1063/1.5142582
|View full text |Cite
|
Sign up to set email alerts
|

Gradient doping of sulfur in Sb2Se3 nanowire arrays as photoelectrochemical photocathode with a 2% half-cell solar-to-hydrogen conversion efficiency

Abstract: Exploring Sb2Se3 as a photoelectrochemical (PEC) photocathode for water reduction has recently attracted much attention, mainly due to its excellent photophysical properties and perfect band structure matching with water reduction potential. Whereas significant achievements have been made in improving its photocurrent density, the PEC performance remains poor mostly due to the low onset potential or low fill factor. Here, we fabricated S doped Sb2Se3 nanowire arrays with a gradient S concentration (grad-S:Sb2S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…The open-circuit voltage ( V OC ) of the pristine film was found to be −0.13 V vs. SCE (0.49 V vs. RHE, Supplementary Equations (S1) and (S2) ), while the V OC values of treated Sb 2 Se 3 films shifted toward more positive potentials of about −0.05 V vs. SCE (0.57 V vs. RHE, Supplementary Equation (S3) ). For most Sb 2 Se 3 -based photoelectrodes, V OC values less than 0.5 V vs. RHE have been typically reported [ 20 , 21 , 22 , 23 ]. This V OC deficiency could be related to different material aspects such as (a) low quality of the single-phase Sb 2 Se 3 , a high concentration of defects and grain boundaries along with the presence of secondary crystalline or amorphous phases, which are harmful to the device performance [ 8 , 20 , 21 , 22 , 23 ]; (b) insufficient structure optimization, e.g., lattice mismatch, and an inauspicious band offset between p-type Sb 2 Se 3 and n-type CdS grown using a chemical bath [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The open-circuit voltage ( V OC ) of the pristine film was found to be −0.13 V vs. SCE (0.49 V vs. RHE, Supplementary Equations (S1) and (S2) ), while the V OC values of treated Sb 2 Se 3 films shifted toward more positive potentials of about −0.05 V vs. SCE (0.57 V vs. RHE, Supplementary Equation (S3) ). For most Sb 2 Se 3 -based photoelectrodes, V OC values less than 0.5 V vs. RHE have been typically reported [ 20 , 21 , 22 , 23 ]. This V OC deficiency could be related to different material aspects such as (a) low quality of the single-phase Sb 2 Se 3 , a high concentration of defects and grain boundaries along with the presence of secondary crystalline or amorphous phases, which are harmful to the device performance [ 8 , 20 , 21 , 22 , 23 ]; (b) insufficient structure optimization, e.g., lattice mismatch, and an inauspicious band offset between p-type Sb 2 Se 3 and n-type CdS grown using a chemical bath [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…For most Sb 2 Se 3 -based photoelectrodes, V OC values less than 0.5 V vs. RHE have been typically reported [ 20 , 21 , 22 , 23 ]. This V OC deficiency could be related to different material aspects such as (a) low quality of the single-phase Sb 2 Se 3 , a high concentration of defects and grain boundaries along with the presence of secondary crystalline or amorphous phases, which are harmful to the device performance [ 8 , 20 , 21 , 22 , 23 ]; (b) insufficient structure optimization, e.g., lattice mismatch, and an inauspicious band offset between p-type Sb 2 Se 3 and n-type CdS grown using a chemical bath [ 22 ]. Several authors reported the V OC values of about 0.6 V vs. RHE measured in Na 2 SO 4 electrolytes with pH values lying between 5 and 6.5 [ 39 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several strategies have been presented in the literature such as Te incorporation for defect passivation, [5] sulfurization treatment for improved photovoltage [6] and gradient sulfur doping in Sb2Se3. [7] More fundamental insights into the basic optoelectronic properties for defect passivation/suppression for Sb2Se3, however, have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%